KESAMAAN KOMUNITAS BURUNG DI KAWASAN CAGAR ALAM PANGI BINANGGA KABUPATEN PARIGI MOUTONG - n, Nurdiansyah; Labiro, Elhayat; s, Sustri (Universitas Tadulako, 2019)
Indonesia has a high diversity of birds. Indonesia is known as one of the places where the world's biodiversity is concentrated, so it has been dubbed